PEMEDIASIAN MODAL SOSIAL PADA PENGARUH KEPEMIMPINAN TRANSFORMASIONAL DAN EMPLOYEE ENGAGEMENT TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR - Priyono, Bambang Suko; ., Basukianto; ., Kis Indriyaningrum (Proceeding SENDI_U, 2021)
This study was conducted to examine and analyze the effect of Transformational Leadership and Employee Engagement on Organizational Citizenship Behavior with Social Capital as the intervening variable. The sampling technique used is a census with 101 people as respondents. The instrument test was carried out through validity and reliability tests. The result is that all indicators in each variable are declared valid, and all variables are reliable. By using multiple linear regression model, five hypotheses were tested with the following results, 1) transformational leadership has a positive effect on social capital, 2) employee engagement has a positive effect on social capital, 3) transformational leadership has a positive effect on organizational citizenship behavior, 4) employee engagement has a positive effect on organizational citizenship behavior, and 5) social capital has a positive effect on organizational citizenship behavior. The indirect effect test was conducted through the Sobel test, the results of which showed that social capital was significantly able to become an intervening variable on the influence of transformational leadership and employee engagement on organizational citizenship behavior.